Professional qualifications offered by the second-degree schools in the state of Rio Grande do Norte from 1971 to 1996 (Research, Society and Development, 2020)
In this paper we try to analyze the professional qualifications offered as second-degree teaching by the state of Rio Grande do Norte (RN) from 1971 to 1996. The bibliographical study is based on Araújo (2010) and Germano (2011), among others, and the source of documental analysis was collected in the State Secretary of Education and Culture of RN. Our main purpose was to analyze if the qualifications offered were connected to the demands of the labor market, in order to understand how much economics interfered in public education in this period. To achieve this, we questioned: did the labor Market directly interfere in the second-degree courses offered by the state of RN? The results showed us that, though RN offered professional qualification in different categories, these offers did not originate directly from the demands of the labor market, and the reason behind this result is that there were fewer offers related to the primary economic sector (who had a major increase during the 1970´s and 1980´s) when compared to the offers related to tertiary sector.